2022
DOI: 10.3390/cancers14153798
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Deep Learning Prediction of Overall Survival in Non-Small-Cell Lung Cancer Using Contrast-Enhanced Computed Tomography

Abstract: Patient outcomes of non-small-cell lung cancer (NSCLC) vary because of tumor heterogeneity and treatment strategies. This study aimed to construct a deep learning model combining both radiomic and clinical features to predict the overall survival of patients with NSCLC. To improve the reliability of the proposed model, radiomic analysis complying with the Image Biomarker Standardization Initiative and the compensation approach to integrate multicenter datasets were performed on contrast-enhanced computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In the whole population, we obtained cross-validation C-indexes of 0.79, 0.63, and 0.80 for the radiomic, clinical, and clinical-radiomic models. These results are quite encouraging in comparison to previous studies, reporting sometimes lower validation C-indexes [55,56] that reached 0.75 applying a deep-learning methodology [57]. Moreover, we showed that the radiomic score was an independent predictor of OS also in homogeneous populations according to the presence or absence of specific driver gene alteration, as previously reported [15,17].…”
Section: Discussionsupporting
confidence: 88%
“…In the whole population, we obtained cross-validation C-indexes of 0.79, 0.63, and 0.80 for the radiomic, clinical, and clinical-radiomic models. These results are quite encouraging in comparison to previous studies, reporting sometimes lower validation C-indexes [55,56] that reached 0.75 applying a deep-learning methodology [57]. Moreover, we showed that the radiomic score was an independent predictor of OS also in homogeneous populations according to the presence or absence of specific driver gene alteration, as previously reported [15,17].…”
Section: Discussionsupporting
confidence: 88%
“…Hou and colleagues [25] constructed a deep learning model with five hidden layers (20-26-32-26-20 architecture) to predict overall survival in patients with pathologically proven NSCLC at all stages. The input layer consisted of eight radiomic features (based on pre-treatment contrast-enhanced chest CT) and five clinical features.…”
Section: Survival Assessmentmentioning
confidence: 99%
“…Radiologists and nuclear medicine doctors see radiomics as having the potential to provide a quantitative signature of tumors, that are often impossible to be detected by human experts [23]. Therefore, radiomics features have been used in the diagnosis and prognosis of multiple cancer types, including those of the breast [24,25], prostate [26], lung [27], head and neck [28], rectal [29], and others. Numerous studies have validated the predictive power of IBSI radiomics features for generalization to multiple cancer types.…”
Section: Related Workmentioning
confidence: 99%